ICRP Publication 131: Stem cell biology with respect to carcinogenesis aspects of radiological protection. (June 2016) - Hendry, J.H.; Niwa, O.; Barcellos-Hoff, M.H.; Globus, R.K.; Harrison, J.D.; Martin, M.T.; Seed, T.M.; Shay, J.W.; Story, M.D.; Suzuki, K.; Yamashita, S.
Current knowledge of stem cell characteristics, maintenance and renewal, evolution with age, location in 'niches', and radiosensitivity to acute and protracted exposures is reviewed regarding haematopoietic tissue, mammary gland, thyroid, digestive tract, lung, skin, and bone. The identity of the target cells for carcinogenesis continues to point to the more primitive and mostly quiescent stem cell population (able to accumulate the protracted sequence of mutations necessary to result in malignancy), and, in a few tissues, to daughter progenitor cells. Several biological processes could contribute to the protection of stem cells from mutation accumulation: (1) accurate DNA repair; (2) rapid induced death of injured stem cells; (3) retention of the intact parental strand during divisions in some tissues so that mutations are passed to the daughter differentiating cells; and (4) stem cell competition, whereby undamaged stem cells outcompete damaged stem cells for residence in the vital niche. DNA repair mainly operates within a few days of irradiation, while stem cell replications and competition require weeks or many months depending on the tissue type. This foundation is used to provide a biological insight to protection issues including the linear-non-threshold and relative risk models, differences in cancer risk between tissues, dose-rate effects, and changes in the risk of radiation carcinogenesis by age at exposure and attained age.